Hypertension drives parenchymal β‐amyloid accumulation in the brain parenchyma. (9th January 2014) - Bueche, Celine Z.; Hawkes, Cheryl; Garz, Cornelia; Vielhaber, Stefan; Attems, Johannes; Knight, Robert T.; Reymann, Klaus; Heinze, Hans‐Jochen; Carare, Roxana O.; Schreiber, Stefanie
Abstract There is substantial controversy regarding the causative role of amyloid β (Aβ) deposition in Alzheimer's disease (AD). The cerebrovasculature plays an important role in the elimination of Aβ from the brain and hypertension is a well‐known risk factor for AD. In spontaneously hypertensive stroke‐prone rats (SHRSP), an animal model of chronic arterial hypertension, cerebral small vessel disease (CSVD) leads to age‐dependent parenchymal Aβ accumulation similar to that observed in AD. These data approve the neuropathological link between CSVD and AD, confirm the challenge that parenchymal Aβ deposition is a specific marker for AD and disclose the meaning of SHRSP as valid experimental model to investigate the association between hypertension, CSVD, and Aβ plaques.